2009
DOI: 10.1016/j.cell.2009.10.034
|View full text |Cite
|
Sign up to set email alerts
|

RNF12 Is an X-Encoded Dose-Dependent Activator of X Chromosome Inactivation

Abstract: In somatic cells of female placental mammals, one X chromosome is inactivated to minimize sex-related dosage differences of X-encoded genes. Random X chromosome inactivation (XCI) in the embryo is a stochastic process, in which each X has an independent probability to initiate XCI, triggered by the nuclear concentration of one or more X-encoded XCI-activators. Here, we identify the E3 ubiquitin ligase RNF12 as an important XCI-activator. Additional copies of mouse Rnf12 or human RNF12 result in initiation of X… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

10
280
2
3

Year Published

2010
2010
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 219 publications
(295 citation statements)
references
References 34 publications
10
280
2
3
Order By: Relevance
“…S7 C and E), suggesting a crucial role of Rnf12 transcription in the expression of Xist during preimplantation stage. In addition, RNF12 can specifically activate Xist expression in the paternal X chromosome during iXCI and also prevent excessive up-regulation of Xist with a rapid feedback mechanism (24,33). Together, these data show that Rnf12 overexpression can be used to compensate impaired iXCI by fine-tuning Xist expression in IVF female embryos.…”
Section: Resultsmentioning
confidence: 70%
“…S7 C and E), suggesting a crucial role of Rnf12 transcription in the expression of Xist during preimplantation stage. In addition, RNF12 can specifically activate Xist expression in the paternal X chromosome during iXCI and also prevent excessive up-regulation of Xist with a rapid feedback mechanism (24,33). Together, these data show that Rnf12 overexpression can be used to compensate impaired iXCI by fine-tuning Xist expression in IVF female embryos.…”
Section: Resultsmentioning
confidence: 70%
“…51 RNAi mediated knockdown of Scc3/SA protein levels can also result in altered transcription of cohesinregulated genes, perhaps by altering cohesin's insulator function. 52 Similarly to the finding that protein levels of X-linked genes can be critical for the regulation of XCI, 53 precise SA2 expression levels could be important for XCI choice.…”
Section: Discussionmentioning
confidence: 94%
“…The involvement of Rnf12 in maintenance of XCI via the BMP/TGF-β pathway is particularly intriguing, because Rnf12 has a known role in initiation of XCI that is independent of TGF-β: During ES cell differentiation, Rnf12 induces XIST expression by promoting ubiquitylation and degradation of REX1, a pluripotency factor that represses XIST transcription in ES cells (14). Whereas REX1 is no longer expressed in differentiated cells, our results indicate that Rnf12 has retained its role as an XIST activator in differentiated cells through augmentation of BMP signaling.…”
Section: Discussionmentioning
confidence: 99%
“…We found that the BMP signaling pathway is required for maintenance of XIST expression. Furthermore, we show that Rnf12, a known regulator of BMP signaling (13), modulates XIST expression in adult cells, suggesting that the role of Rnf12 as a regulator of XIST during initiation of X-chromosome inactivation in ES cells (14,15) is retained in differentiated cells through control of BMP signaling.…”
mentioning
confidence: 96%